Association Between the Tobacco Cessation Training and Oral Cancer Knowledge Level with Tobacco Use Related Behaviour Among the 4th Year Dental Undergraduates-A Cross Sectional Study in Dhaka, Bangladesh - Chowdhury, Mohammad Tawfique Hossain; Croucher, Ray (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Tobacco use is widespread in Bangladesh. Dental Professionals could act on different levels of tobacco control activities. AIM: to explore prevalence and attitudes towards tobacco and identified the association of tobacco use related behaviour with the level of tobacco cessation training and level of knowledge of oral cancer among 4th year dental undergraduates of Dhaka, Bangladesh. Methods: This was a self reported cross-sectional questionnaire based survey. Global Health Professional Survey (GHPS) questionnaire and Humphris Oral Cancer Knowledge Scale questionnaire were used in this survey. Fourth year dental undergraduates studying in six dental colleges in Dhaka completed the questionnaire in April and May, 2007. Results: Response rate was 93%. Current prevalence of cigarette and chewing tobacco is 24% and 10% respectively. Male respondents were the predominant user of tobacco and had the less positive attitudes towards tobacco cessation than female. This study also shows that knowledge and training did not have any influence over tobacco related behaviour. Conclusions: In this sample of Bangladeshi dental students, high prevalence of tobacco use but strong positive attitudes towards tobacco cessation was reported. Review of policy and dental curriculum is needed as it is identified that training and oral cancer knowledge did not seem to have impact over tobacco use related behaviour. DOI = 10.3329/jom.v9i1.1423 Â J MEDICINE 2008; 9 : 31-36